Implementation of a program for the prevention and control of HAIs - Hernández Torres, Francisca Angélica (Interdisciplinary Journal of Epidemiology and Public Health, 2023)
Health Care Associated Infections (HAI), are considered a public health problem, including those conditions that the patient was not incubating prior to hospital admission and that are acquired as a result of clinical care and can extend even after the patient is discharged. In the context of the COVID-19 pandemic, there was an increase in the number of HAIs worldwide due to the demand for health care for critically ill patients.HAIs are adverse events in clinical care that can evolve into sentinel events resulting in disability or death for the patient; in addition, they have economic implications for the patient, family, and the health sector.It is necessary to implement measures for the prevention and control of these infections that reduce costs and most importantly, are preventable complications "No one should die from an HAI".